STRATEGI KOMUNIKASI PEMASARAN EVENT ORGANIZER RUPA SUARA CAHAYA DALAM MENDAPATKAN KEPERCAYAAN KLIEN - Mochamad Taufiq Kolil; Muhammad Daffa Asyam; Muhammad Aalim Rosaail; Raul Adiputra; Falik Izza Hadar Arza (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Udayana, 2025)
Event organizers experience a significant growth rate of around 14% annually so that the competition is very tight, one of which is experienced by the event organizer Rupa Suara Cahaya to gain trust from clients. The purpose of this study is to determine the marketing communication strategy carried out by Rupa Suara Cahaya is gaining trust from clients. This study uses qualitative method. The informants are Hendra Setya as the owner of CV. Ulfa Merdeka, Raden Ahmad Fuad as the head of the Rupa Suara Cahaya division and several clients. Data analysis uses data reduction, data presentation, and drawing conclusion. The result of the research on Rupa Suara Cahaya’s marketing communication strategy in gaining client trust are: (1) advertising, using social media such as Instagram, Youtube and TikTok. (2) Sales promotion, by providing discounts and giving away free products according to the concept of an event. (3) Public relations, all staf employee are tasked with disseminating communication and implementing various program related to other parties, and maintaining good communication and relationship with clients or the public. (4) Personal selling, conducting sales presentations of a product or service to potentional clients both face to face and using digital platforms. (5) Direct marketing, using social media such as Instagram, TikTok, Youtube and the Rupa Suara Cahaya Website. The Rupa Suara Cahaya team can open a pop-up both to sell tickets directly while providing an explanation of the event concept, showing promotional videos, or offering exclucive merchandise to buyers on site.